Analysis of the Effect of Risk Management and Compliance Practices on Financial Performance and Corporate Reputation in the Financial Industry in Indonesia - Judijanto, Loso; Hairuddin, Sitti Hartati; Subhan, Subhan; Sipayung, Baren (Eastasouth Institute, 2024)
This study examines the impact of risk management and compliance practices on the financial performance and corporate reputation of financial institutions in Indonesia. Utilizing a quantitative approach, data were collected from 160 financial institutions through a structured questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results indicate that both risk management and compliance practices significantly enhance financial performance and corporate reputation. Specifically, risk management practices have a stronger positive impact on both outcomes compared to compliance practices. These findings underscore the necessity for financial institutions to integrate comprehensive risk management and compliance strategies into their operations to achieve financial stability and bolster their reputation. The study provides valuable insights for practitioners and policymakers, highlighting the critical role of these practices in fostering long-term sustainability and success in the financial industry.